Thermoelectric properties of gradient polymer composites with nano-inclusions fabricated by laser assisted sintering. (26th January 2017) - Shishkovsky, I V; Scherbakov, V I; Saraeva, I N; Ionin, A A
Abstract: Selective laser sintering (SLS) was used to prepare porous gradient polymer nanocomposites consisting of a polyetheretherketone (PEEK) matrix doped with alternating layers of Ni and Cu nanoparticles. Optimal regimes of such 3D-fabrication were determined. The functional graded (FG) structure of sintered parts was observed by optical and scanning electron microscopy and EDX microanalysis. Temperature dependence of electro-physical properties was studied for alternating ferromagnetic/non-magnetic layers (up to 10 layers) into 3D-graded samples derived from Ni-PEEK-Cu powders. Temperature dependences for the real part of the dielectric permeability and loss tangent were found to have a hysteresis character.